4.3k views
5 votes
-3x + 40 = -23

A) -21
B)5.6
C)21
D)-32.3

User Success
by
5.4k points

1 Answer

3 votes

Answer:

C) 21

General Formulas and Concepts:

Pre-Algebra

Order of Operations: BPEMDAS

  1. Brackets
  2. Parenthesis
  3. Exponents
  4. Multiplication
  5. Division
  6. Addition
  7. Subtraction
  • Left to Right

Equality Properties

Explanation:

Step 1: Define

-3x + 40 = -23

Step 2: Solve for x

  1. Isolate x term: -3x = -63
  2. Isolate x: x = 21

Step 3: Check

Plug in x into the original equation to verify it's a solution.

  1. Substitute in x: -3(21) + 40 = -23
  2. Multiply: -63 + 40 = -23
  3. Add: -23 = -23

Here we see that -23 does indeed equal -23.

∴ x = 21 is the solution to the equation.

User Ronag
by
5.7k points